2012
DOI: 10.5539/ijbm.v7n19p45
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ERP Successful Implementation on Employees' Productivity, Service Quality and Innovation: An Empirical Study in Telecommunication Sector in Jordan

Abstract: The aim of this research paper is to identify the effect of ERP successful implementation on employees' productivity, service quality and innovation. Data were collected via questionnaires from 129 employees working in the Jordanian telecommunication organizations. The collected data were analyzed using descriptive statistics and structural equation model to test the study hypotheses using AMOS 16.0. The results of this study revealed that there is a significant effect of organizational impact on employees' pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Increases in productivity are often the chief motivation for companies to introduce information technology (Swierczek and Shrestha, 2003; Black and Lynch, 2001; Brynjolfsson and Yang, 1996; Jalava and Pohjola, 2007; Qutaishat et al , 2012; Subriadi et al , 2013). Organisations invest in HRM systems to make effective use of their human capital and, thereby, to enhance employee productivity (Datta et al , 2005; Liao et al , 2009).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Increases in productivity are often the chief motivation for companies to introduce information technology (Swierczek and Shrestha, 2003; Black and Lynch, 2001; Brynjolfsson and Yang, 1996; Jalava and Pohjola, 2007; Qutaishat et al , 2012; Subriadi et al , 2013). Organisations invest in HRM systems to make effective use of their human capital and, thereby, to enhance employee productivity (Datta et al , 2005; Liao et al , 2009).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Huang et al (2009) found that improved process efficiency is evident in firms adopting ERP systems in the post-implementation period. Other research by Qutaishat et al (2012) confirmed that ERP benefits in terms of efficiency and effectiveness benefits led to increased employee productivity, innovation and service quality. In this study, user effectiveness benefits from ERP are defined as the benefits of better management of user’s work tasks and meeting business process objectives gained from using ERP (Table I).…”
Section: Literature Review and Research Modelmentioning
confidence: 88%
“…In today's competitive world, organizations place emphasis on employee productivity improvement strategies (Qutaishat, Khattab, Zaid, & Al-Manasra, 2012). Productivity has been recognized as a key value outcome in the IT business value literature for superior firm performance and to achieve competitive advantage (Lempinen & Rajala, 2014).…”
Section: Employee Productivitymentioning
confidence: 99%